Long-term outcomes of high-volume stapled hemorroidopexy to treat symptomatic hemorrhoidal disease - Alessandro Sturiale; Raad Dowais; Bernardina Fabiani; Claudia Menconi; Felipe Celedon Porzio; Virginia Coli; Gabriele Naldini (Annals of Coloproctology, 2023)
Purpose The study aimed to assess the long-term results of the stapled hemorrhoidopexy (SH) using high-volume devices equipped with innovative technology, evaluating recurrence rate, complications rate, and patients’ satisfaction. Methods All the patients who underwent SH using high-volume devices (TST Starr plus, Touchstone International Medical Science Corp., Ltd.) for II to IV symptomatic hemorrhoidal disease from November 2012 to December 2014 were enrolled. Between December 2019 and January 2020, all of them were phone called to come to undergo a proctological reevaluation and asked to fill some questionnaires about hemorrhoidal prolapse recurrence, symptoms recurrence, and surgery satisfaction. Results Fifty-nine patients with a mean age of 47 years completely answered the questionnaires. Twenty-two of them accepted to come to undergo a proctological reevaluation while 27 preferred to answer only by phone due to their referred wellbeing. The median follow-up was 70.5 months (range, 60–84 months). The recurrence rate was 5.1% with a mean satisfaction level after surgery was 9.1 (range, 0–10) and 84.7% of patients whose satisfaction scored ≥8. The mean value of Cleveland Global Quality of Life assessment was 0.79 (range, 0.71–0.93). There were no cases of new onset of impaired anal continence after surgery. Conclusion The new generation high-volume devices to perform SH resulted to be safe and effective for II to IV degree hemorrhoidal prolapse leading to a lower long-term recurrence rate with an evident reduction of postoperative complications in comparison with the low-volume SH.